A battery separator and preparation method thereof, and secondary battery
A battery separator with a modified coating of metal oxide and/or metal nitride and ionic liquid carbide addresses the shuttle effect in lithium-sulfur batteries, improving cycle and discharge performance by effectively suppressing polysulfide loss.
Patent Information
- Application Number
- CN202310111232.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-02-14
AI Technical Summary
The 'shuttle effect' in lithium-sulfur batteries, where polysulfides dissolve through the diaphragm causing active material loss and lithium metal corrosion, limits their practical application, and current separator improvements are not ideal in mitigating this issue.
A battery separator with a modified coating comprising metal oxide and/or metal nitride and ionic liquid carbide, with a specific mass ratio, is applied to the separator substrate to suppress the shuttle effect and absorb polysulfides.
The modified separator effectively inhibits the shuttle effect, enhancing the cycle and discharge performance of lithium-sulfur batteries by improving polysulfide retention.
Smart Images

Figure BDA0004076857180000081
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a battery separator and a preparation method thereof, and a secondary battery. Background Art
[0002] With the growing energy demand and excessive environmental problems, as well as the continuous miniaturization of electronic devices, the rapid development of portable electronic information products and new energy vehicles, the development of sustainable and clean energy has attracted more and more attention, such as wind energy, solar energy, tidal energy, etc. However, due to the uncontrollability of these energy sources, they cannot meet the large-scale application needs. Traditional lithium-ion batteries such as lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMnO4), and lithium nickel oxide (LiNiO2) batteries can no longer meet the overall needs due to insufficient energy and inconvenience.
[0003] Lithium-sulfur secondary batteries use elemental sulfur or sulfur-containing materials as the positive electrode active material. Among them, sulfur is widely distributed in nature, and it has the advantages of being environmentally friendly and having a high theoretical specific energy. It is considered to be a secondary battery with a relatively promising development prospect. Different from the ion deintercalation principle of lithium-ion batteries, the charging and discharging process of lithium-sulfur batteries is an electrochemical mechanism, with sulfur as the positive electrode reactant and lithium as the negative electrode. During discharge, the negative electrode reaction is that lithium loses electrons to become lithium ions, and the positive electrode reaction is that sulfur reacts with lithium ions and electrons to form polysulfides. The potential difference between the positive and negative electrode reactions is the lithium-sulfur battery. Under the action of an applied voltage, the positive and negative electrode reactions of the lithium-sulfur battery proceed in reverse, which is the charging process. During the charging and discharging process, polysulfides will dissolve through the diaphragm, which will cause loss of active materials on the one hand, and on the other hand, polysulfides will pass through the diaphragm to the negative electrode, corrode lithium metal, and aggravate the growth of lithium dendrites. This is the "shuttle effect", which is also one of the key issues currently limiting the practical application of lithium-sulfur batteries.
[0004] As an important component of the battery, the separator is the key to improving the performance of the battery in all aspects. At present, one of the more common methods is to load materials that have adsorption and catalytic effects on polysulfides in the battery separator or interlayer to avoid the "shuttle effect", but the improvement effect is not very ideal. Summary of the invention
[0005] Therefore, the technical problem to be solved by the present invention is to overcome the defect of the prior art that the effect of avoiding the "shuttle effect" of lithium-sulfur batteries is not ideal, thereby providing a battery separator and a preparation method thereof, and a secondary battery.
[0006] To this end, the present invention provides the following technical solutions:
[0007] The present invention provides a battery separator, comprising a separator substrate and a modified coating coated on one side of the separator substrate, wherein the modified coating comprises metal oxide and / or metal nitride, ionic liquid carbide,
[0008] Wherein, the mass ratio of (metal oxide and / or metal nitride) to ionic liquid carbide is 0.9-1:1.
[0009] Optionally, the metal oxide is selected from at least one of aluminum oxide, cobalt oxide, iron oxide and nickel oxide;
[0010] The metal nitride is selected from at least one of cobalt nitride, titanium nitride and magnesium nitride.
[0011] Optionally, the ionic liquid carbide is obtained by calcining an ionic liquid;
[0012] Optionally, the calcination temperature is 600-800°C and the calcination time is 3-6h;
[0013] Optionally, the ionic liquid is at least one of 1-butyl-3-methylimidazole ionic liquids and 1-tetradecyl-3-methylimidazole ionic liquids. Typically, but not limited to, the ionic liquid may be 1-tetradecyl-3-methylimidazole bromide, 1-tetradecyl-3-methylimidazole chloride, 1-butyl-3-methylimidazole chloride, and the like.
[0014] Optionally, the modified coating further comprises a conductive agent and a binder;
[0015] Optionally, the mass ratio of (metal oxide and / or metal nitride+ionic liquid carbide):conductive agent:binder=7:1.9-2.1:0.9-1.1;
[0016] Optionally, the modified coating has a thickness of 150-200 μm.
[0017] Optionally, the conductive agent is at least one of conductive carbon black, Ketjen black, and acetylene black;
[0018] And / or, the binder is at least one of polyvinylidene fluoride and binder LA133;
[0019] And / or, the diaphragm matrix is a polyethylene diaphragm, a polypropylene diaphragm or a polyethylene / polypropylene composite diaphragm.
[0020] The present invention also provides a method for preparing the above-mentioned battery separator, comprising the following steps:
[0021] S1, mixing the raw materials of the modified coating (i.e., metal oxide and / or metal nitride, ionic liquid carbide, conductive agent, binder) with an organic solvent to obtain a modified slurry;
[0022] S2, coating the modified slurry on one side surface of the separator substrate, and drying to obtain the battery separator.
[0023] Optionally, the solid content of the modified slurry is 52-65wt%;
[0024] And / or, the organic solvent is at least one of N-methylpyrrolidone and dimethyl sulfoxide.
[0025] Optionally, in step S2, the drying temperature is 55-60°C and the drying time is 10-12h.
[0026] The present invention also provides a secondary battery, comprising the battery separator mentioned above or the battery separator prepared by the above preparation method.
[0027] Optionally, the secondary battery is a lithium-sulfur battery.
[0028] The metal oxide and / or metal nitride used in the present invention can be obtained through commercial channels or prepared by self-production, and the preparation methods are all conventional in the field. The pore size is generally micropores or mesopores, and the larger the specific surface area, the better. The materials obtained or prepared through conventional channels can basically meet the use requirements.
[0029] For example, taking cobalt nitride as an example, the specific steps of its preparation method are as follows:
[0030] (1) dissolving cobalt acetate and polyvinyl pyrrolidone in ethylene glycol and stirring for 2-3 hours;
[0031] (2) transferring the mixture into an autoclave and maintaining it at 180-200° C. for 10-12 hours, then cooling the reactants to room temperature, collecting the precipitate by centrifugation, washing it with ethanol and distilled water several times, and then drying it at 45-50° C. for 20-24 hours, and finally collecting the product for later use;
[0032] (3) calcining the product in a muffle furnace, heating to 550±5° C. at a heating rate of 3±1° C. / min and maintaining the temperature for 4 hours to obtain mesoporous cobalt oxide;
[0033] (4) Finally, in a tubular furnace, N2 gas is introduced, and the mixture is first heated to 280-300°C at a heating rate of 5±1°C / min, and then heated to 350-400°C at a heating rate of 1±0.5°C / min and kept at a constant temperature for 3-4 hours to obtain mesoporous cobalt nitride.
[0034] The precursor is prepared by the hydrothermal method, and the operation method is relatively simple.
[0035] The composition, structure and preparation method of the secondary battery provided in the present invention are well known in the art.
[0036] Taking a lithium-sulfur battery as an example, typically and non-limitingly, the lithium-sulfur battery comprises a positive electrode, a negative electrode, a separator and an electrolyte;
[0037] The positive electrode active material is elemental sulfur; the positive electrode also includes a conductive agent and a binder, and its preparation method is as follows: the positive electrode active material (elemental sulfur), the conductive agent (Super P) and the binder (PVDF) are weighed in a certain mass ratio (7:2:1), a certain ratio of NMP is added and ground into slurry, and then coated on the surface of aluminum foil with a scraper, and finally placed in a vacuum oven and dried at 60°C for 12 hours to obtain a positive electrode sheet.
[0038] The metallic lithium sheet is used as the negative electrode.
[0039] The electrolyte composition is lithium bis(trifluoromethanesulfonate)imide (LITFSI) / ethylene carbonate (EC)+dimethyl carbonate (DMC) solution.
[0040] The preparation method is as follows: assembling and molding a button-type simulated battery in a glove box filled with argon gas.
[0041] The technical solution of the present invention has the following advantages:
[0042] The battery separator provided by the present invention comprises a separator substrate and a modified coating coated on one side of the separator substrate, wherein the modified coating comprises metal oxide and / or metal nitride, and ionic liquid carbide, wherein the mass ratio of (metal oxide and / or metal nitride) to ionic liquid carbide is 0.9-1:1. The separator modified by the metal oxide and / or metal nitride and ionic liquid carbide with a specific ratio can effectively suppress the "shuttle effect", absorb polysulfide, and make the lithium-sulfur battery using the modified battery separator have good cycle performance, and effectively improve the discharge performance of the lithium-sulfur battery.
[0043] The battery separator provided by the present invention can further improve the cycle performance and discharge performance of the lithium-sulfur battery through the limitation of metal nitride, metal oxide and ionic liquid. DETAILED DESCRIPTION
[0044] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0045] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0046] Example 1
[0047] A battery separator comprises a separator substrate and a modified coating coated on one side of the separator substrate, wherein the mass ratio of cobalt nitride to ionic liquid carbide in the raw materials of the modified coating is 1:1.
[0048] The preparation method and specific step parameters of the battery separator are as follows:
[0049] Preparation of cobalt nitride: (1) dissolve 10 g of cobalt acetate and 1 g of polyvinyl pyrrolidone in 55 mL of ethylene glycol and stir for 3 hours; (2) transfer the mixture to an autoclave and keep it at 200°C for 12 hours, then cool the reactants to room temperature, collect the precipitate by centrifugation, wash it several times with ethanol and distilled water, then dry it at 50°C for 24 hours, and finally collect the product for use (mesoporous cobalt oxide); (3) calcine the product in a muffle furnace, heat it to 550°C at a heating rate of 3°C / min and keep it at a constant temperature for 4 hours, and cool it to room temperature; (4) finally, introduce gas N2 into a tubular furnace, first heat it to 300°C at a heating rate of 5°C / min, and then heat it to 400°C at a heating rate of 1°C / min and keep it at a constant temperature for 4 hours to obtain mesoporous cobalt nitride.
[0050] Preparation of ionic liquid carbide: 1-butyl-3-methylimidazole chloride was calcined at 700°C in a muffle furnace for 4 hours to obtain ionic liquid carbide.
[0051] Coating: The prepared cobalt nitride, ionic liquid carbide, Super P (manufacturer's special high model Super-P) and PVDF (manufacturer Guangdong Candlelight model HSV900) are dissolved in NMP at a ratio of 3.5:3.5:2:1 to form a slurry (solid content of 52%), and then the slurry is coated on a common diaphragm (manufacturer Celgard model 2400) with a scraper. The coating thickness is 200μm, and the slurry is placed in a vacuum oven at 60°C and dried for 12 hours to obtain a battery diaphragm, and then cut into 16mm discs for standby use.
[0052] Example 2
[0053] A battery separator, compared with Example 1, the only difference is that the mass ratio of cobalt nitride, ionic liquid carbide, Super P and PVDF in the slurry is 3.2:3.8:2:1.
[0054] Example 3
[0055] A battery separator, compared with Example 1, the only difference is that the mass ratio of cobalt nitride, ionic liquid carbide, Super P and PVDF in the slurry is 3.4:3.6:2:1.
[0056] Example 4
[0057] A battery separator, compared with Example 1, the only difference is that aluminum oxide (manufacturer Aladdin, model Al2O3) is used instead of cobalt nitride.
[0058] Example 5
[0059] A battery separator, compared with Example 1, the only difference is that the preparation steps of cobalt nitride do not include step (4), that is, cobalt oxide is used instead of cobalt nitride.
[0060] Example 6
[0061] A battery separator, compared with Example 1, the only difference is that 1-tetradecyl-3-methylimidazolium bromide is used instead of 1-butyl-3-methylimidazolium chloride.
[0062] Example 7
[0063] A battery separator, compared with Example 1, the only difference is that in the preparation step of the ionic liquid carbide, the calcination temperature is 600° C. and the calcination time is 6 hours.
[0064] Example 8
[0065] A battery separator, compared with Example 1, the only difference is that in the preparation step of the ionic liquid carbide, the calcination temperature is 800° C. and the calcination time is 3 hours.
[0066] Comparative Example 1
[0067] A battery separator, compared with Example 1, the only difference is that an equal amount of cobalt nitride is used to replace the ionic liquid carbide.
[0068] Comparative Example 2
[0069] A battery separator, compared with Example 1, the only difference is that an equal amount of ionic liquid carbide is used instead of cobalt nitride.
[0070] Test Case
[0071] The battery separators provided in the embodiments of the present invention and the comparative examples were assembled into button-type lithium-sulfur batteries, and their cycle performance and discharge performance were tested. The specific test method was as follows:
[0072] Preparation of button cell: The positive electrode uses elemental sulfur, Super P and PVDF in a certain mass ratio (7:2:1), and a certain ratio of NMP is added to grind into slurry with a solid content of 52%, and then coated on aluminum foil with a scraper to a coating thickness of 200μm, and finally placed in a vacuum oven at 60℃ for 12 hours to obtain the positive electrode sheet. A metal lithium sheet is used as the negative electrode, and the battery separator provided in each embodiment and comparative example is used as the separator. The electrolyte is a lithium sulfur special electrolyte purchased from Suzhou Duoduo Chemical Technology Co., Ltd., and assembled into a button type simulation battery (model CR2032) in a glove box filled with argon.
[0073] After the assembled simulated battery was left standing at room temperature for 12 hours, it was tested in the charge and discharge voltage range of 1.7-2.8V. The specific test steps were: charge and discharge test at a rate of 0.1C, with a charge cut-off voltage of 2.8V and a discharge cut-off voltage of 1.7V.
[0074] The specific test results are shown in the table below:
[0075] Table 1
[0076]
[0077] Note: Comparative Example 3 is a conventional diaphragm in Example 1 without the modified coating.
[0078] The test results in the above table show that the present invention can effectively inhibit the "shuttle effect" and absorb polysulfides by modifying the diaphragm with metal oxides and / or metal nitrides and ionic liquid carbides at the same time, so that the lithium-sulfur battery using the modified battery diaphragm provided in the embodiment has good cycle performance and effectively improves the discharge performance of the lithium-sulfur battery. By comparing the data of Example 4, Example 5 with Example 1, and Example 6 with Example 1, it can be seen that the combination of metal nitride and 1-butyl-3-methylimidazole ionic liquid carbide has the best modification effect on the diaphragm.
[0079] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A lithium-sulfur battery separator, characterized in that: The invention comprises a membrane substrate and a modified coating coated on one side of the membrane substrate, wherein the modified coating comprises metal oxide and / or metal nitride, ionic liquid carbide, The mass ratio of (metal oxide and / or metal nitride) to ionic liquid carbide is 0.9-1:1; and the ionic liquid carbide is obtained by calcining the ionic liquid.
2. The lithium-sulfur battery separator according to claim 1, characterized in that: The metal oxide is selected from at least one of aluminum oxide, cobalt oxide, iron oxide and nickel oxide; The metal nitride is selected from at least one of cobalt nitride, titanium nitride and magnesium nitride.
3. The lithium-sulfur battery separator according to claim 1, characterized in that: The calcination temperature is 600-800°C and the calcination time is 3-6h; And / or, the ionic liquid is at least one of 1-butyl-3-methylimidazole ionic liquid and 1-tetradecyl-3-methylimidazole ionic liquid.
4. The lithium-sulfur battery separator according to any one of claims 1 to 3, characterized in that: The modified coating also includes a conductive agent and a binder; And / or, the modified coating has a thickness of 150-200 μm.
5. The lithium-sulfur battery separator according to claim 4, characterized in that: In the modified coating, the mass ratio of (metal oxide and / or metal nitride + ionic liquid carbide): conductive agent: binder = 7:1.9-2.1:0.9-1.1; And / or, the conductive agent is at least one of conductive carbon black, Ketjen black and acetylene black; And / or, the binder is at least one of polyvinylidene fluoride and binder LA133; And / or, the diaphragm matrix is a polyethylene diaphragm, a polypropylene diaphragm or a polyethylene / polypropylene composite diaphragm.
6. A method for preparing a lithium-sulfur battery separator according to any one of claims 1 to 5, characterized in that: The steps include: S1, mixing various raw materials of the modified coating with an organic solvent to obtain a modified slurry; S2, coating the modified slurry on one side surface of the separator substrate, and drying to obtain the battery separator.
7. The method for preparing a lithium-sulfur battery separator according to claim 6, characterized in that: The solid content of the modified slurry is 52-65wt%; And / or, the organic solvent is at least one of N-methylpyrrolidone and dimethyl sulfoxide.
8. The method for preparing a lithium-sulfur battery separator according to claim 6 or 7, characterized in that: In step S2, the drying temperature is 55-60°C and the drying time is 10-12 hours.
9. A secondary battery, characterized in that: The invention comprises the battery separator according to any one of claims 1 to 5 or the lithium-sulfur battery separator prepared by the preparation method according to any one of claims 6 to 8.
